Autophagy-Related Atg8 Localizes to the Apicoplast of the Human Malaria Parasite Plasmodium falciparum - Kitamura, Kei (Public Library of Science, 2012)

(untitled)
Autophagy is a membrane-mediated degradation process, which is governed by sequential functions of Atg proteins. Although Atg proteins are highly conserved in eukaryotes, protozoa possess only a partial set of Atg proteins. Nonetheless, almost all protozoa have the complete factors belonging to the Atg8 conjugation system, namely, Atg3, Atg4, Atg7, and Atg8. Here, we report the biochemical properties and subcellular localization of the Atg8 protein of the human malaria parasite Plasmodium falciparum (PfAtg8). PfAtg8 is expressed during intra-erythrocytic development and associates with membranes likely as a lipid-conjugated form. Fluorescence microscopy and immunoelectron microscopy show that PfAtg8 localizes to the apicoplast, a four membrane-bound non-photosynthetic plastid. Autophagosome-like structures are not observed in the erythrocytic stages. These data suggest that, although Plasmodium parasites have lost most Atg proteins during evolution, they use the Atg8 conjugation system for the unique organelle, the apicoplast.